2015
DOI: 10.1016/j.envpol.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of various metal(loid)s via multiple exposure pathways on children living near a typical lead-acid battery plant, China

Abstract: a b s t r a c tManufacture of lead-acid batteries is of widespread interest because of its emissions of heavy metals and metalloids into environment, harming environmental quality and consequently causing detrimental effects on human health. In this study, exposure pathways and health risks of children to heavy metal(loid)s (Pb, Cd, As, etc) were investigated based on field sampling and questionnaire. Pb was one of the most abundant elements in children's blood, with an elevated blood lead level of 12.45 mg dL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(73 citation statements)
references
References 48 publications
9
64
0
Order By: Relevance
“…In this study, carcinogenic risk induced by Cr, As, and Cd exceeded the maximal acceptable risk level, indicating that carcinogenic risk from these three metals in drinking water is higher than the non-carcinogenic risk from seven metals from drinking water in both areas. This result is similar to most other related studies (Zhang et al 2014a, b;Cao et al 2015), but different from the study conducted in Shenzhen, China, which concluded that the non-cancer risk was higher than the cancer risk from heavy metals in drinking water (Lu et al 2015).…”
Section: Non-carcinogenic Risk Assessmentsupporting
confidence: 53%
“…In this study, carcinogenic risk induced by Cr, As, and Cd exceeded the maximal acceptable risk level, indicating that carcinogenic risk from these three metals in drinking water is higher than the non-carcinogenic risk from seven metals from drinking water in both areas. This result is similar to most other related studies (Zhang et al 2014a, b;Cao et al 2015), but different from the study conducted in Shenzhen, China, which concluded that the non-cancer risk was higher than the cancer risk from heavy metals in drinking water (Lu et al 2015).…”
Section: Non-carcinogenic Risk Assessmentsupporting
confidence: 53%
“…Our results confirmed that exposure to toxic metals from soils and sediments would cause high potential ecological risks and health risks in this area, although the results would inevitably be affected by the inherent uncertainty in risk assessment (USEPA, 1989;Cao et al, 2015). In this study, bioavailability of the metals in soils and sediments was not considered, which might result in an overestimation of the potential risks.…”
Section: Risk Characteristics Of Contaminationsupporting
confidence: 57%
“…If HQ 1, adverse health effects would be unlikely to be experienced, whereas potential non-carcinogenic effects would occur when HQ > 1 (Cao et al, 2015).…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…In the present study, we adapted the health risk assessment models of the U.S. EPA to evaluate the health risks of the heavy metals. The average daily doses through ingestion (ADD ing ) (mg/kg/day), inhalation (ADD inh ) (mg/kg/day), and dermal contact (ADD dermal ) (mg/kg/day) were calculated as follows (Cao et al, 2015):…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%